Aqueous Extract of Leaves and Flowers of Acmella caulirhiza Reduces the Proliferation of Cancer Cells by Underexpressing Some Genes and Activating Caspase-3 - Huiny Miriane Tienoue Fotso; Mary-Ann Mbong Angie; Françoise Raïssa Ntentie; Inelle Makamwe; Ferdinand Lanvin Edoun Ebouel; Emmerencia Kenjing Ndansack; Enyong Julius Oben (Biochemistry Research International)
The increasing prevalence of cancers and the multiple side effects of cancer treatments have led researchers to constantly search for plants containing bioactive compounds with cell death properties. This work aimed at evaluating the antiproliferative effect of an Acmella caulirhiza extract. After evaluation of the in vitro antioxidant potential of the three extracts of Acmella caulirhiza (aqueous (AE-Ac), hydroethanolic (HEE-Ac), and ethanolic (EE-Ac)) through the scavenging of DPPH● and NO● radicals, the extract with the best antioxidant activity was selected for bioactive compound assessment and antiproliferative tests. Subsequently, the cytotoxic activity was evaluated on the viability of breast (MCF-7), brain (CT2A, SB-28, and GL-261), colon (MC-38), and skin (YUMM 1.7 and B16-F1) cancer lines using the MTT method. Then, the line where the extract was the most active was selected to evaluate the expression of certain genes involved in cancerogenesis by RT-PCR and the expression of cleaved caspase-3 involved in cell death mechanism by western blot. The AE-Ac showed the best scavenging activity with IC50s of 0.52 and 0.02 for DPPH● and NO●, respectively. This AE-Ac was found to contain alkaloids, flavonoids, and tannins and was more active on YUMM 1.7 cells (IC50 = 149.42 and 31.99 μg/mL for 24 and 48 h, respectively). Results also showed that AE-Ac downregulated the expression of inflammation (IL-1b p=0.017 and IL-6 p=0.028), growth factors (PDGF p=0.039, IGF p=0.034, E2F1p=0.038, and E2F2p=0.016), and antiapoptotic protein genes (Bcl-2 p=0.028 and Bcl-6 p=0.039). The cleaved caspase-3 was positively modulated by the AE-Ac inducing thus cell death by apoptosis. AE-Ac showed inhibitory effects on the expression of genes involved in cancer progression making it a potential health intervention agent that can be exploited in cancer therapy protocols.